Lexicography in a Multilingual South Africa - Various, Various (Lexikos, 1999)
On 12 April 1996 the State Language Services organized a language planning seminar, Lexicography as a Financial Asset in a Multilingual South Africa, held at the Bureau of the Woordeboek van die Afrikaanse Taal in Stellenbosch. A special feature of this workshop was the active participation not only of linguists and lexicographers involved in the academic and practical side of producing dictionaries, but also of those with commercial interests in this area, viz. publishers and marketers of dictionaries. An important part of the seminar was the contributions on the lexicographic needs of each of the eleven official languages of the Republic of South Africa. This seminar was followed by a consultative meeting for stakeholders arranged by the Pan South African Language Board (PANSALB) on 31 October 1997 in Johannesburg. The purpose of the meeting was to explain to participants the state of the legislation concerning lexicography units, to inform participants of the language plan for the Republic of South Africa and the role of lexicography in it, to make participants aware of the preparation needed to establish a lexicography unit, and to obtain the view of participants regarding important lexicographic matters by means of a questionnaire and discussions. This meeting was an important precursor to two further meetings which PANSALB arranged in the Johannesburg Civic Centre, namely the Lexicographic Meeting of the Existing Lexicographic Units of South Africa on 19 and 20 March 1998 and the Lexicographic Meeting of the Languages which do not already have a Lexicographic Unit on 14 and 15 May 1998. The delegates participated in establishing norms for the recognition of existing and new lexicography units, and for the provision of personnel to, and for the state subsidisation of lexicography units. Regulations for the lexicography units were also discussed. The papers presented at these two meetings provide a synopsis of the state of lexicography in the different official languages of the Republic of South Africa. The assignment for the first occasion was to outline the mission, history and present situation of the existing units, namely of Afrikaans, English, isiNdebele, Sepedi, isiXhosa and isiZulu. The assignment for the second occasion was to delineate the state of lexicography in those languages which do not have lexicography units, namely Sesotho, Setswana, siSwati, Tshivenda and Tsonga. Adapted and updated extracts from the documentation of these meetings are published here with the kind permission of PANSALB and of the presenters of the different papers. These are preceded by an exposition of the procedure for the establishing of the lexicography units for the eleven official languages of the Republic of South Africa. PANSALB was established in 1995 in terms of the Pan South African Language Board Act (No. 59 of 1995). To make provision for, inter alia, the creation of lexicography units by PANSALB, the Pan South African Language Board Amendment Act (No. 10 of 1999) was assented to this year. The aims of PANSALB are: (a) to promote respect for and ensure the implementation of the following principles: (i) the creation of conditions for the development and for the promotion of the equal use and enjoyment of all the official South African languages; (ii) the extension of those rights relating to language and the status of languages which before 27 April 1994 were restricted to certain regions; (iii) the prevention of the use of any language for the purposes of exploitation, domination or division; (iv) the promotion of — (aa) multilingualism; and (bb) the provision of translation and interpreting facilities; (v) the fostering of respect for languages spoken in the Republic other than the official languages, and the encouragement of their use in appropriate circumstances; and (vi) the non-diminution of rights relating to language and the status of languages existing before 27 April 1994; (b) to further the development of the official South African languages; (c) to promote respect for and the development of other languages used by communities in South Africa, and languages used for religious purposes; (d) to promote knowledge of and respect for the provisions and principles of the Constitution relating directly or indirectly to language matters; (e) to promote respect for multilingualism in general; and (f) to promote the utilisation of South Africa's language resources.The National Lexicography Units - Existing and ProspectiveM.B. KumaloBureau of the Woordeboek van die Afrikaanse TaalB.P.D. Gabriels, A.E. Cloete and W.F. BothaDictionary Unit for isiNdebeleP.B. SkhosanaDictionary Unit for South African EnglishPenny SilvaSepedi Dictionary ProjectD.J. Prinsloo and K.J. MashamaiteXhosa Dictionary ProjectT.X. MfaxaZulu Dictionary ProjectA.C. NkabindeThe State of Lexicography in SesothoM.A. MolelekiThe State of Lexicography in SetswanaM.R. MalopeThe State of siSwati LexicographyP.M. LubisiThe State of Tshivenda LexicographyA. MawelaThe State of Xitsonga LexicographyD.I. MathumbaKeywords: pansalb; lexicography units; pan south african language board act; 1995; pan south african language board amendment act; 1998; afrilex; bureau of the woordeboek van die afrikaanse taal; dictionary unit for isindebele; dictionary unit for south african english; northern sotho dictionary unit; xhosa dictionary project; zulu dictionary project; sesotho lexicography; setswana lexicography; siswati lexicography; tshivenda lexicography; tsonga lexicography